2010
DOI: 10.1002/pssa.201026086
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of InN grown on templates with controlled surface polarities

Abstract: The structural and optical properties of InN layers grown on GaN/sapphire templates with controlled Ga‐/N‐polar surfaces are investigated. Raman spectroscopy and XRD reciprocal space map analysis suggest that the InN layers were grown strain free with a high crystal quality. A line shape analysis of the A1(LO) Raman mode yields to a decreasing carrier concentration for the sample grown on Ga‐polar substrate. Low temperature photoluminescence measurements exhibit a shift to lower energies of the luminescence ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Different incorporation of defects depending on the polarity is well known for many materials including GaN, InN, and ZnO. [14][15][16] It has been shown that in many cases the surface with the polarity of the cation has a much lower unintentional doping rate compared to that of the anion side. 17 Cathodoluminescence spectra of the N-and Ga-polar areas of sample A were recorded in order to confirm these findings and are shown in Fig.…”
Section: Figurementioning
confidence: 99%
“…Different incorporation of defects depending on the polarity is well known for many materials including GaN, InN, and ZnO. [14][15][16] It has been shown that in many cases the surface with the polarity of the cation has a much lower unintentional doping rate compared to that of the anion side. 17 Cathodoluminescence spectra of the N-and Ga-polar areas of sample A were recorded in order to confirm these findings and are shown in Fig.…”
Section: Figurementioning
confidence: 99%
“…23,24 This indicates that comparable to GaN or InN, increased point defect incorporation occurs on the anion side of polar AlN or increased incorporation of nonradiative defects occurs on the cation side of AlN. 25 In conclusion, AlN-based lateral polarity structures were grown by MOCVD on sapphire substrates. Control of the polarity was achieved by using a patterned low temperature AlN buffer layer: Al-polar domains grew on top of the LT buffer while N-polar domains grew on bare sapphire.…”
mentioning
confidence: 95%
“…In the investigated pressure range of 20 bars, the growth rate falls almost by one order of magnitude, suggesting that even if this approach is feasible to stabilize and integrate MQW with vastly different partial pressures, it might not viable for thick material layer growth. As demonstrated, the stabilization of indium-rich InGaN can be addressed by the high-pressure CVD, 95,96,94,97,42 using a pulsed injection of the precursor scheme, which minimizes gas phase reactions and has the significant advantage to prevent phase segregations. This scheme facilitates the control of the growth process on a sub-monolayer level and enables a thorough real-time optical analysis of surface chemistry processes during growth.…”
Section: Inn and Indium-rich Ingan Epilayers And Heterostructuresmentioning
confidence: 99%